Design and optimization of the extended true single-phase clock-based prescaler - Yu, Xiao Peng (2009)
The power consumption and operating frequency of the extended true single-phase clock (E-TSPC)-based frequency divider is investigated. The short-circuit power and the switching power in the E-TSPC-based divider are calculated and simulated. A low-power divide-by-2/3 unit of a prescaler is proposed and implemented using a CMOS technology. Compared with the existing design, a 25% reduction of power consumption is achieved. A divide-by-8/9 dual-modulus prescaler implemented with this divide-by-2/3 unit using a 0.18-µm CMOS process is capable of operating up to 4 GHz with a low-power consumption. The prescaler is implemented in low-power high-resolution frequency dividers for wireless local area network applications.